Clinical outcomes and prognostic factors of patients with advanced hepatocellular carcinoma treated with sorafenib as first‐line therapy: A Korean multicenter study. Issue 7 (15th July 2014) - Lee, Sangheun; Kim, Beom Kyung; Kim, Seung Up; Park, Soo Young; Kim, Ja Kyung; Lee, Hyun Woong; Park, Jun Yong; Kim, Do Young; Ahn, Sang Hoon; Tak, Won Young; Kweon, Young Oh; Lee, Jung Il; et al.
Abstract Background and Aim Sorafenib is recommended as a standard treatment for advanced hepatocellular carcinoma (HCC). The efficacy and safety of sorafenib as a first‐line therapy in Korean patients with advanced HCC were investigated. Methods From 2007 to 2012, 86 patients with advanced HCC (Barcelona Clinic Liver Cancer stage C) treated with sorafenib as a first‐line therapy were enrolled from five tertiary hospitals. Predictors of overall survival (OS) and progression‐free survival (PFS) were analyzed. Results The median age was 59.5 years, and 71 (82.6%) were males; 57 (66.3%) patients were in Child–Pugh class A. The median OS and PFS were 5.0 (range 4.0–5.9) and 3.2 (range 2.6–3.7) months, respectively. Regarding OS, Child–Pugh class A (6.0 vs 2.8 months), tumor diameter < 5 cm (6.0 vs 4.3 months), baseline α‐fetoprotein < 200 ng/mL (5.8 vs 4.1 months), and the advent of hand‐foot‐skin reaction of ≥ grade 2 (5.9 vs 4.0 months) were independent favorable predictors (all P < 0.05). Similarly, regarding PFS, Child–Pugh class A (4.3 vs 2.1 months), tumor diameter < 5 cm (3.9 vs 2.8 months), baseline α‐fetoprotein < 200 ng/mL (5.6 vs 2.8 months), and the advent of hand‐foot‐skin reaction of ≥ grade 2 (4.5 vs 2.6 months) were independent favorable predictors (all P < 0.05). All toxicities during sorafenib treatment were manageable. Conclusions Because the efficacy of sorafenib seems marginal in Korean patients with treatment‐naïve HCC, how to select candidates with favorable outcomes should be further investigated.